2019
DOI: 10.1016/j.ebiom.2019.09.021
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbiota from colorectal cancer patients enhances the progression of intestinal adenoma in Apcmin/+ mice

Abstract: BackgroundAccumulating evidence points to a close relationship between gut dysbiosis and colorectal cancer (CRC). As >90% of CRC develop from adenoma, we aimed to investigate the crucial role of imbalanced gut microbiota on the progression of intestinal adenoma.MethodsThe Apcmin/+ mice gavage with phosphate-buffered saline (PBS), feces from healthy controls or CRC patients after antibiotic cocktails. The intestinal tissues were isolated for histopathology, western blotting, and RNA-seq. The microbiota of feces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 51 publications
4
88
0
Order By: Relevance
“…This pathway is classified into canonical ( β-catenin dependent) and non-canonical ( β-catenin independent) [9] . Consistent with Li and colleagues' results [3] , Jiang and colleagues [10] also showed that the canonical Wnt pathway played an essential role in different stages of tumour development.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…This pathway is classified into canonical ( β-catenin dependent) and non-canonical ( β-catenin independent) [9] . Consistent with Li and colleagues' results [3] , Jiang and colleagues [10] also showed that the canonical Wnt pathway played an essential role in different stages of tumour development.…”
supporting
confidence: 76%
“…This process can not only provide energy for the microbiota but also result in the release of short-chain fatty acids (SCFAs), including butyrate, which could be used for metabolic needs by the colonocytes, maintain mucosal integrity, and suppress inflammation and carcinogenesis [6] . Analysing the faecal supernatant of patients with colorectal cancer, Li and colleagues [3] found that the relative abundance of Roseburia spp and Clostridium spp was lower than that in the faecal supernatant of healthy patients, consistent with Wang and colleagues' findings [7] , whereas the relative abundance of Akkermansia spp and Ruminococcus spp was higher, consistent with Weir and colleagues' results [8] . Similarly, the number of pathogenic bacteria increased after FMT, whereas the number of bacteria secreting SCFAs (such as Ruminococcus spp, Roseburia spp, and Clostridium cluster XlVa spp) and the production of SCFAs in the caecum decreased, which could be one of the reasons for the destruction of intestinal mucosal barrier and the occurrence of chronic inflammation in Apc min/ + mice after transplantation.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The increase in abundance Clostridium XlVa could alleviate the pathogenesis of depression and cancers. Clostridium XlVa was signi cantly lower in CRC patients [77]. Clostridium XIVa was overrepresented in healthy control subjects [36,82].…”
Section: Discussionmentioning
confidence: 88%